(untitled) (Annals of Medical Research, 2021)
Aim: We evaluated the level of knowledge on diabetic retinopathy (DR) and management approaches of primary care physicians with important roles in preventive health services.Material and Methods: Using a Google form, a 14-item questionnaire was prepared to the family physicians’ knowledge about DR and the examination tools they use and their management approach. This questionnaire was sent to 92 family physicians in Turkey via the What’s App Messenger.Results: According to the questionnaire responses, 90 (97.8%) of the family physician centers had a Snellen chart and 91 (98.9%) a direct ophthalmoscope. Among the physicians, 79 (85.9%) did not perform visual acuity examinations for diabetic patients, and 39 (42.4%) did not use an ophthalmoscope. While 34 (37.0%) of the surveyed physicians did not refer diabetic patients to an ophthalmologist for DR examinations at all, only 22 (23.9%) referred patients to an ophthalmologist at the time of initial diagnosis and 19 (20.7%) referred patients at 1 year after the initial diagnosis. 10 (10.8%) of the surveyed physicians referred patients to an ophthalmologist at 2-year intervals, 4 (4.3%) at 6-month intervals, and three (3.3%) at over 2-year intervals. Among the physicians, 64 (69.6%), 57 (62.0%), and 63 (68.5%) were not familiar with the stages of DR, fundus fluorescein angiography, and laser treatment for DR, and 60 (65.2%) did not know how to perform intraocular injection treatment methods. A total of 87 (94.6%) physicians stated a need for training programs in DR.Conclusion: DR, an eye complication of diabetes mellitus, is not well understood by family physicians, and more than half of physicians referred their patients to an ophthalmologist either late after diagnosis or not at all. It is therefore important for family physicians to undergo training programs on DR to increase their effectiveness in primary health care services.